Reverse Phase High Performance Liquid Chromatography Determination of Imatinib Mesylate α-Form in Bulk and Pharmaceutical Formulations - Venkat Rao, S.; Rambabu, C.; Ramu, G.; Ch, K.; Ganesh, M. (Asian Journal of Chemistry, 2011)
A rapid, precise, economical and accurate HPLC method for estimation of mephedrone in bulk and formulations was developed and validated. The chromatographic resolution of imatinib mesylate α-form was achieved using acetonitrile: 0.1M potassium dihydrogen phosphate buffer, (85:15 v/v) as a mobile phase UV detection at 254 nm and hypersil C18 column flow rate 1 mL/ min. Recovery of Imatinib mesylate α-form from its formulation dosage form was greater than 99.48 %. Calibration curve was linear (r2 = 0.9984) over the concentration ranging from 10 to 60 μg/mL of imatinib mesylate. The method has an accuracy of greater than 99 % and limit of detection and limit of quantification of 0.83300 μg/mL and 2.77400 μg/mL respectively. Results of the analysis were validated statistically and recovery studies were found to be satisfactory.